TRANSFER TEKNOLOGI BUDIDAYA TANAMAN JAGUNG TERHADAP PAGUYUBAN GAPOKTAN SEKAMPUNG (PAGAS), DESA SUMBERSARI, KECAMATAN SEKAMPUNG, LAMPUNG TIMUR - Kartahadimaja, Jaenudin; Erlinda Syuriani, Eka; Wahyudi, Anung; Novridha Andini, Siti; Tianigut, Gut; Septiana, Septiana; Hidayatullah Zaini, Akbar; Adimiharja, Jamaludin; Hanapi Fadliyansyah, Muhamad; Fadilla, Reza (Politeknik Negeri Lampung, 2022)
National corn demand from year to year always increases in line with the development of industries that require raw materials derived from corn, especially the animal feed industry. Lampung Province is the third national corn producer after East Java and Central Java with a total production in 2021 of 2.83 million tons of dry beans. East Lampung Regency is the main corn producing district in Lampung Province with a total production of 950.234 tons. Sekampung sub-district is one of the areas in East Lampung Regency whose corn productivity is still low compared to other sub-districts. One of the reasons for the low productivity of maize in Sekampung Sub-district is because the maize cultivation technology applied by farmers under the PAGAS Gapoktan is very diverse and many are still very traditional, with the use of seeds of low quality. The purpose of PKM is to transfer knowledge and technology of intensive corn cultivation and provide skills on how to produce or produce high quality corn seeds, both for hybrid, synthetic and composite corn seeds. The service method used includes showing several picture slides, simulations with writing demonstrations, discussions, and showing several demonstration plots. The results of the PKM show that there is an increase in the mastery of knowledge and skills both cognitively, affectively, and psychomotorically. The knowledge ability and attitude change of the target audience about corn cultivation increased to 100%, while psychomotorically on how to produce hybrid, synthetic and composite corn seeds rose from zero to around 72.87%. Keywords: Maize, Cultivation intensive, technology transfer